Comparison of MRT-research materials of brain in multiple sclerosis and lupus erythematosus - Yu. N. Lisitsyna; V. M. Alifirova (Бюллетень сибирской медицины)
It appears that sometimes it is difficult to perform differential diagnostics of multiple sclerosis and autoimmune illness. 29 patients were surveyed with lupus erythematosus and 29 patients hue suffer from multiple sclerosis. Here are presented our own results of magnetic resonance imaging of the brain of there patients. It is discovered that existence of nidus of T2 signal increase doesn’t appear to be a specific sign.